HUBUNGAN MARKETING MIX TERHADAP KEPUTUSAN KONSUMEN SAYURAN HIDROPONIK DI CRISPY FARM KECAMATAN BANYUMANIK KABUPATEN SEMARANG - Kiki Irawati; Bayu Nuswantara (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2019)
In modern society a healthy lifestyle is one measure of quality standards. A healthy lifestyle can be started by consuming organic vegetables. Crispy Farm is a place for cultivating organic vegetables with Hydroponic techniques, by means of hydroponic aquaculture which is currently increasingly being applied among homes. Organic vegetables are vegetables that are produced from natural ingredients without using synthetic chemicals. This study aims to analyze the effect of marketing mix which includes: prices, products, promotions and distribution on consumer decisions to buy Hydroponic vegetables at Crispy Farm. This research uses quantitative methods, with data collection techniques using primary data and secondary data. The research area was established in Banyumanik District, namely Jl. Tejosari, Gedawang Village, Banyumanik District, Semarang Regency, Central Java. The research was conducted from October to December 2018. The results showed that the factors that had a significant effect were the price of hydroponic vegetables (X1), Vegetable Hydroponic Products (X2) and Promotions Conducted by Crispy Fram (X3) on Decisions of Hydroponic Vegetable Consumers. While the factors that have no significant effect are the distribution of Hydroponic Vegetables (X4) to the decisions of hydroponic vegetable consumers (Y).